Techno-economic and environmental evaluation of nano calcium carbonate production utilizing the steel slag - Lee, Jaeseo; Ryu, Kyung Hwan; Ha, Heung Yong; Jung, Kwang-Deog; Lee, Jay H. (ELSEVIER SCI LTD, 2020)
This work investigates the possibility of commercialization of a recently proposed nano calcium carbonate production process as an improved process. The analyzed process uses steel slag instead of limestone as the calcium source to produce nano calcium carbonate and comprises a calcium carbonation process and a NaCl electrolysis process. CO2 reduction impact and techno-economic feasibility of the system are analyzed to investigate its feasibility. The new process is expected to reduce the CO2 emission by about 8 %, compared to the conventional process of making the nano calcium carbonate. In addition, unit cost of production for the new process is 484 USD/ton indicating that it is economically feasible. Sensitivity and scenario analyses are performed with respect to the type of electricity sources and the capital cost of the electrolysis system, which are the key contributors to the overall cost.
Keywords: LIFE-CYCLE ASSESSMENT; CO2 CAPTURE; MINERAL CARBONATION; WASTE-WATER; DIOXIDE; SEQUESTRATION; TECHNOLOGIES; PERFORMANCE; CONVERSION; FIXATION